Forging peace : intervention, human rights and the management of media space - Price, Monroe E., 1938-; Thompson, Mark, 1959- (International communications., 2002)
Since the 1990s, a number of conflicts have focused attention on the media's fole in promoting war and chaos. This text comprises case studies and legal analysis of the steps that the UN, NATO and other organizations have taken to build an independent media in the wake of human rights violations.